2013
DOI: 10.3174/ajnr.a3581
|View full text |Cite
|
Sign up to set email alerts
|

Early White Matter Changes in Childhood Multiple Sclerosis: A Diffusion Tensor Imaging Study

Abstract: BACKGROUND AND PURPOSE:Loss of integrity in nonlesional white matter occurs as a fundamental feature of multiple sclerosis in adults. The purpose of our study was to evaluate DTI-derived measures of white matter microstructure in children with MS compared with age-and sex-matched controls by using tract-based spatial statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…63,64 A correlation between reduced FA and impaired performance in mathematics 56 and with impaired processing speed 65 has been reported in 34 young patients with paediatric-onset multiple sclerosis. Findings from two studies of tract-based analyses have showed reduced FA in normal-appearing white matter in 14 paediatric patients 66 and ten paediatric patients 67 compared with age-matched and sex-matched healthy controls. Taken together, findings from these studies suggest that myelin architecture might be disrupted early in multiple sclerosis, but large serial studies and tract-based analyses are needed to further assess the effect of multiple sclerosis on myelinated pathways over time.…”
Section: Mri In Paediatric Multiple Sclerosismentioning
confidence: 99%
“…63,64 A correlation between reduced FA and impaired performance in mathematics 56 and with impaired processing speed 65 has been reported in 34 young patients with paediatric-onset multiple sclerosis. Findings from two studies of tract-based analyses have showed reduced FA in normal-appearing white matter in 14 paediatric patients 66 and ten paediatric patients 67 compared with age-matched and sex-matched healthy controls. Taken together, findings from these studies suggest that myelin architecture might be disrupted early in multiple sclerosis, but large serial studies and tract-based analyses are needed to further assess the effect of multiple sclerosis on myelinated pathways over time.…”
Section: Mri In Paediatric Multiple Sclerosismentioning
confidence: 99%
“…Since its description in 2006, tract-based spatial statistics (TBSS) 15 , has been applied to multisubject spatial analysis of DTI data examining neurological and cognitive correlates of WM degradation in MS [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . These studies broadly support the suggestion that disconnection of cortical or subcortical grey matter by diffuse and focal damage of interconnecting white matter may be an important factor contributing to physical disability and cognitive dysfunction in MS 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, FA was computed for the a priori regions of interest (ROIs) by averaging the FA of each voxel within the ROI mask (combining the Freesurfer labels contained in Table generated the ROI masks). The a priori ROIs for the region‐wise FA analyses, selected based on previous literature, were frontal, parietal, occipital, and temporal lobe WM, as well as the thalamus and corpus callosum …”
Section: Methodsmentioning
confidence: 99%
“…The a priori ROIs for the region-wise FA analyses, selected based on previous literature, were frontal, parietal, occipital, and temporal lobe WM, as well as the thalamus and corpus callosum. 11,15,[30][31][32] Tractography analysis was then performed with FMRIB's Diffusion Toolbox (FDT) to compute the probability of streamlines or connections between Freesurfer-defined seeds and targets (exclusion masks). 33 The following parameters within FDT were used: curvature threshold = .2 mm, maximum steps per sample = 2,000, step length = .5 mm, and total samples = 5,000.…”
Section: Image Processingmentioning
confidence: 99%